5x-5=4(x+3)

Simple and best practice solution for 5x-5=4(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-5=4(x+3) equation:


Simplifying
5x + -5 = 4(x + 3)

Reorder the terms:
-5 + 5x = 4(x + 3)

Reorder the terms:
-5 + 5x = 4(3 + x)
-5 + 5x = (3 * 4 + x * 4)
-5 + 5x = (12 + 4x)

Solving
-5 + 5x = 12 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-5 + 5x + -4x = 12 + 4x + -4x

Combine like terms: 5x + -4x = 1x
-5 + 1x = 12 + 4x + -4x

Combine like terms: 4x + -4x = 0
-5 + 1x = 12 + 0
-5 + 1x = 12

Add '5' to each side of the equation.
-5 + 5 + 1x = 12 + 5

Combine like terms: -5 + 5 = 0
0 + 1x = 12 + 5
1x = 12 + 5

Combine like terms: 12 + 5 = 17
1x = 17

Divide each side by '1'.
x = 17

Simplifying
x = 17

See similar equations:

| 36y+6=26 | | X=0.22-0.22+1.0x | | 6x+5=2x+31 | | f(2)=8-3x | | F=3(-5)+7(2) | | X=0.2-0.22+1.0x | | x^2+4-6x-4=0 | | 41-3v=4v+6 | | 2520+24x=18y | | 64q-40= | | f(0)=8-3x | | (10x-12)-(4x-10)= | | 3z+5=4v+6 | | 24p-27= | | log[4]2^1/3 | | 2y+5=5y-7 | | 42g+35= | | 4q+5p=50 | | 15+20x=7+18x | | 10y+90= | | 4x-4=13x-122 | | 15+20x=-7+18X | | 0.5x-0.4y=6.2 | | (y+3)=5y+8 | | X+2=4x+16 | | 3p^2q+15pq^2-12pq=0 | | 0.18x+0.13y=0.04 | | 49m^2=14m+24 | | 2(x+6)=-2 | | 2x+(3+4)-3y=x | | 6+8=214 | | 2a-12=7a+8 |

Equations solver categories